2019
DOI: 10.1097/md.0000000000017256
|View full text |Cite
|
Sign up to set email alerts
|

The role of echocardiography and 99mTc-HDP scintigraphy in non-invasive diagnosis of cardiac amyloidosis

Abstract: Rationale:Cardiac amyloidosis, considered for the last years to be a rare disease, is one of the determinants of HFpEF. The non-specific clinical presentation and the difficulties related to endomyocardial biopsy have made cardiac amyloidosis an underdiagnosed clinical entity. Improvement of non-invasive diagnostic techniques and the development of new therapies increased clinical awareness for this form of restrictive cardiomyopathy. We here summarize echocardiography and 99mTc-HDP scintigraphy findings in 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Six of the studies reported on low-voltage QRS complexes. Costache and colleagues (2019 ) in the Roman case series identified low-voltage QRS complexes in all six subjects. In the Zhang and colleagues (2021 ) retrospective cohort study EKG of the CA group, low-voltage QRS complexes were found in 52% of limb leads and 21% in precordial leads.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Six of the studies reported on low-voltage QRS complexes. Costache and colleagues (2019 ) in the Roman case series identified low-voltage QRS complexes in all six subjects. In the Zhang and colleagues (2021 ) retrospective cohort study EKG of the CA group, low-voltage QRS complexes were found in 52% of limb leads and 21% in precordial leads.…”
Section: Resultsmentioning
confidence: 86%
“…LV hypertrophy was evaluated in four of the studies. In the Costache and colleagues (2019 ) case series, absence of LV hypertrophy was identified on EKG in all six subjects. In contrast, in the Pagourelias and colleagues (2017 ) study, only 5 of the 40 patients demonstrated LV hypertrophy on EKG.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, there is inadequate knowledge on how to diagnose CA and to interpret bone scintigraphy results. This non-invasive diagnostic technique, easy to perform also among older adults 14 , has 99% sensitivity and 86% specificity for cardiac ATTR 15 and has been included as a screening tool for ATTR-CA in the 2016 European Society of Cardiology guidelines for the treatment of heart failure 16 . Worthy of note also are the really poor physicians' awareness of how to diagnose ATTRwt, the most common form of CA among older adults 4 , and the relatively low number of patients sent for specific treatments (already documented among Cardiologists 8 ), probably due to the poor knowledge of which is the target for ATTRwt treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of cardiac involvement in amyloidosis can be challenging due to unspecific or missing clinical manifestations. Although non-invasive imaging modalities such as echocardiography (with speckle-based strain measurement), bone scintigraphy ( 10 ) as well as multi-parametric CMR are widely used today and promise both early and specific detection of cardiac amyloidosis ( 11 , 12 ), invasive EMB still constitutes the gold-standard for the final diagnosis of non-ischemic heart diseases including cardiac amyloidosis ( 13 ). Noteworthy, imaging modalities such as bone scintigraphy and multi-parametric CMR were shown to be valuable tools in differentiating cardiac ATTR from AL amyloidosis if additional information on monoclonal protein studies are available and promise early detection of cardiac amyloidosis ( 9 , 14 ).…”
Section: Methodsmentioning
confidence: 99%